Asas Kepastian Hukum dalam Aturan Sanksi Pelanggaran Pencatatan Perkawinan Undang-Undang Hukum Keluarga Malaysia - Ardiansyah, Ardiansyah (Zaaken: Journal of Civil and Business Law, 2023)
This article discusses the rules of sanctions against marriage registration violations in Malaysia. Unregistered marriages often negate the rights that must be fulfilled for both spouses and children. The imposition of sanctions for those who fail to register their marriages is oriented towards the highly essential welfare to establish legal certainty for Malaysian citizens who enter into marriage. This writing focuses on the violation rules of marriage registration under Article 125 of the Federal Territories Act 303 of Malaysia. This research employs a normative juridical approach with legislative and conceptual approaches using Gustav Radbruch's legal certainty theory. The results of this study indicate that the rules of sanctions for marriage registration violations in Malaysia are highly important and relevant in the application of the principle of legal certainty to protect the rights of citizens who enter into marriage. Â  Â